Geologic Influence on Radon Concentrations Levels in Cave: A Case Study of Mimpi Cave in the Maros Karst of South Sulawesi, Indonesia - S Syarbaini; K Kusdiana; W Wahyudi; D. Iskandar; S. Widodo; S. Dewang (Atom Indonesia, 2023)
Radon gas in the natural environment mainly comes from the release of local bedrock geology and easily accumulate in closed spaces such as basements and caves. This study was performed to investigate the radon concentrations in Mimpi Cave, Bantimurung-Bulusaraung National Park, in the Maros karst area, South Sulawesi, and discussed a possible relationship between the radon concentrations and the local geology. Measurements were carried out using a passive detection technique with CR-39 nuclear tracks detectors by exposing it for a period of three months. The 222Rn levels measured inside the cave ranges from 64.03 Bq m‑3 to 3396.02 Bq m‑3, with an average value of 1075.05 Bq m‑3.The results are comparable with radon concentration in different caves environments reported from other surveys in several countries. Geological background of the Maros Karst areas could sustain the measured radon values, due to the presence of limestone rock with a mineral composition which can lead to higher radon concentrations in Mimpi Cave.